PERENCANAA PRODUKSI PAVING BLOCK DENGAN MENGGUNAKAN MODEL PROGRAM DINAMIS (DYNAMIC PROGRAMMING) DI CV. SHOHAT GORONTALO. - Maru, Aan Yetno; Wolok, Eduar; Lahay, Idham Halid (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2023)
This current research aimed to plan an optimal and scheduled production to minimize defects in production quantities, excess or shortage of production quantities with minimum costs. The method used was Dynamic Progamming to develop optimal scheduling, by forecasting average production using the Autoregressive Integrated Moving Average (ARIMA) model. The ARIMA was employed to forecast the average amount of production data of CV Shohat Gorontalo which were the data for the last 24 weeks or during 6 months. The result obtained was that the minimum cost was always obtained at the inventory figure I = 0, because having less inventory or even no inventory would reduce the total cost due to the small holding costs when compared to production costs. The cost incurred for the production schedule during the July- December of 2023 period was IDR 9,161,954,550. In addition, the data were the optimal result in minimizing production costs using the Dynamic Programming method. Abstract written in English. Abstracts are written in a sequence that contains the purpose of research, the methods used in research, research results, conclusions, suggestions, and research implications. The abstract is concise, concise and written in one paragraph (maximum 200 words) with single space, Times New Roman font and 10 font sizes